Pengaruh Kombinasi Dekokta Rimpang Zingiber officinale var rubrum dan Imperata cylindrica Terhadap Kadar MMP-9 Serum Tikus Wistar Jantan Model Osteoartritis - Adam Bregas Regowo; Merlita Herbani; Doti Wahyuningsih (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: Osteoarthritis is a damage chronic disorder caused by degenerative process and inflammation that lead to the joint cartilage. Previous research showed that red ginger rhizome (Zingiber officinale var rubrum) and cogon grass rhizome (Imperata Cylindrica) had anti-inflammation and antioxidant effects. This research aimed to know the potencial of the combination of red ginger rhizome (Zingiber officinale var rubrum) and cogon grass rhizome (Imperata Cylindrica) (CRGCG) by measuring the OA rats serum Matrix Metalloproteinase-9 (MMP-9). Matrix Metalloproteinase-9 is an enzyme that plays a role in joint cartilage destruction.Methods: 25 male Wistar rats age 4 months divided into 5 groups namely positive control group (PC), negative control group (NC), treatment group 1 recieved dose 9+40 mg/rat/day (T1), treatment group 2 recieve dose 18+40 mg/rat/day (T2), and treatment group 3 recieve dose 36+40 mg/rat/day(T3). Rats were induced with Complete Freund’s Adjuvant (CFA) by 0.1 ml/rat on right knee intraarticular to induce. The administration of CRGCG is given for 10 days. The serum MMP-9 level was assessed by MMP-9 ELISA Kit. Data analyzed using One Way Anova followed by Post Hoc test. The result is significant if p<0.05.Result: The Combination of Red Ginger Rhizome and Cogon Grass Rhizome (CRGCG) on the first treatment (0,85±0,03), second treatment (0,86±0,02) and third treatment (0,84±0,02) able to decrease the serum MMP-9 level significantly (p<0,05).Conclusion: The optimal dose from Combination of Red Ginger Rhizome and Cogon Grass Rhizome (CRGCG) to reduce serum MMP-9 level is dose 9+40 mg/rat/day.Keywords: Cogon Grass, Matrix Metalloproteinase-9, Osteoarthritis, Red Ginger